URGENSI PENDAFTARAN PERALIHAN PEMEGANG HAK TANGGUNGAN PASCA MERGER MENJADI BANK SYARIAH INDONESIA - Palawa, Eventy Velly; Hartini (Faculty of Law, Parahyangan Catholic University, 2023)
The merger of three Islamic state-owned enterprises into Bank Syariah Indonesia (BSI) has impacted the Mortgage Rights execution post-merger. This is partly due to the change in the name of the bank holding the Mortgage Rights before and after the merger. This study examines the obstacles in executing post-merger Mortgage Rights of three state-owned Islamic banks into BSI and the importance of registering the transfer of Mortgage Rights holders post-merger. This research is done with a normative juridical method through document and field studies at the BSI branch in Palangka Raya, which had experienced obstructions in executing Mortgage Rights when the auction application files was returned by the State Wealth Service and Auction Office. The data is analyzed descriptively and obtained from document and field study. It is found that first, one of the obstacles in executing Mortgage Rights by BSI is the difference in the bank’s name on the Mortgage Rights certificate before and after the merger. Secondly, the registration of the transfer of Mortgage Rights is important because a merger is considered as a cause for the transfer of Mortgage Rights due to